Initial Findings of a Multicomponent School Health Intervention in Rural Appalachia: The Greenbrier CHOICES Project - Jones, Emily (Health Educ Behav, 2020)
BACKGROUND. Schools are an important setting for health promotion because they afford children and adolescents numerous opportunities to accumulate the recommended physical activity (PA) minutes and make other health-related decisions, including healthy eating. Unfortunately, there is little evidence of coordinated school-based health interventions in rural Appalachia. The Greenbrier Children’s Health Opportunities Involving Coordinated Efforts in Schools Project was a federally funded, 3-year, multicomponent school-based health intervention focused on PA, healthy eating, and weight management. AIMS. The purpose of this study was to evaluate the impact of Greenbrier Children’s Health Opportunities Involving Coordinated Efforts in Schools on adolescent PA, dietary behaviors, and weight status. METHOD. Measures of PA, dietary behaviors, and body mass index were collected across 14 data points throughout the intervention (including a baseline in Year 1). RESULTS. Participants included 4,633 randomly selected middle school students (M = 2,289, F = 2,344) across the intervention. Baseline to Year 3 findings revealed a 12.8 percentage point increase in students achieving 60 minutes of daily PA. There were no significant differences in either dietary behavior or body mass index. DISCUSSION. Findings provide evidence of the positive impact comprehensive school-based health interventions can have on middle school student health-related behaviors. CONCLUSION. Schools remain an ideal setting for health promotion. Initiatives targeting more than one level of influence on health-related behaviors are more likely to succeed.